Mid-trimester Genetic Amniocentesis: GATA Experience - Güngör, Sadettin; Başer, İskender and Ergün, Ali (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To ev aluate the data about amniocenteses those were perf ormed in our department and to compare indications, procedure related losses and pregnancy outcomes. STUDY DESIGN: The study was carried out at the Department of Obstetrics and Gy necology, Faculty of Medicine, Gülhane Military Medical Academy retrospectively. We studied amniocenteses for chromosomal analysis between 2002 and 2004. The data of the patients were obtained from their records. RESULTS: The mean (±SD) gestational age at amniocentesis was 17.9±1.3 weeks (range 16-22 weeks). The most common primary indications for amniocentesis were advanced maternal age (37.0%) and positiv e screening test result (36.5%). In 1452 of the procedures (99.7%), amniotic f luid was obtained by a single puncture. A chromosomal abnormality was detected in 47 women (3.2%) who pref erred termination of pregnancy. The total f etal loss rate was 0 in 1456 (0.0%) within two weeks f ollowing amniocentesis CONCLUSION: Amniocentesis is a saf e and reliable technique with low f etal loss rates in complicated and uncomplicated pregnancies in our study group.